POSISI PEREMPUAN MINANGKABAU DALAM SISTEM ULAYAT MENURUT ADAT MATRILINEAL DAN SYARAK - Iza Hanifuddin (JURIS (Jurnal Ilmiah Syariah), 2018)
In matrilineal system of Minangkabau, women gain strategic position. Beside the central line of generation, females also act as ‘bundo kanduang’ who have the right to inherit the tribal heritage from the ancestors and have the authority for the tribal land (tanah ulayat). This position needs to be reconsidered in terms of implementation whether it is still relevant to the principles suggested by the genuine tradition since the concept of inheriting the heritage last forever. The Islamic law (syarak) referred by the tradition points out that the women’s position in the doctrine of fiqh (Islamic jurisprudence) should be respected and has equal rights to men in respect to land ownership and authority.